Clinical significance of pectoralis muscle strength in elderly patients with idiopathic pulmonary fibrosis - YURDALAN, SAADET UFUK (My University, 2022)
Introduction: Investigations of muscle dysfunction in patients with idiopathic pulmonary fibrosis (IPF) are limited to peripheral muscles. However, decreased thoracic muscle mass is known and deterioration of chest wall muscle strength is not clear. Objective: The aims of the present study were to evaluate pectoralis muscle strength located on the chest wall and to investigate the relationship of spirometric measurements and respiratory muscle strength with pectoralis muscle strength. Methods: Elderly patient with IPF (mean disease duration 7.47 +/- 7.04 years) and the age-and sex-matched healthy volunteers were recruited in this cross-sectional study. The pulmonary function test was performed by a portable spirometer for spirometric variables and a gas analyzer for diffusing capacity for carbon monoxide (DLCO). Maximal inspiratory (MIP) and expiratory pressure (MEP) were measured with mouth pressure device. Modified Medical Research Council Dyspnea Scale (MMRC) was used to determined dyspnea severity. The pectoralis muscle strength was assessed isometrically during shoulder joint horizontal adduction movement with a hand-held dynamometer. Results: A total of 17 patients with IPF (9 males, mean age 69.06 +/- 3.94 years) and 19 healthy controls (10 males, mean age 70.95 +/- 4.99 years) were included. Patients with IPF had lower pectoralis muscle strength than healthy controls (p<0.001). Significant relationships were found between pectoralis muscle strength and MIP (r=0.79, p<0.001), MEP (r=0.81, p<0.001), FEV1% (r=0.54, p=0.02), FVC% (r=0.68, p<0.003) and DLCO (r=0.61, p=0.009). With multiple linear regression analysis, pectoralis muscle strength was the only independent predictor of FVC% (adjusted R-2=0.37, p<0.05). Conclusion: In patients with IPF, pectoralis muscle strength decreases and is associated with pulmonary function. In particular pectoralis muscle strength is likely to have an important impact on FVC%. Therefore, we consider that this test should be included routinely in chest diseases and rehabilitation clinics.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Göğüs Hastalıkları ve Allerji; Medicine; Health Sciences; Internal Medicine Sciences; Chest Diseases and Allergy; SOLUNUM SİSTEMİ; Klinik Tıp; Klinik Tıp (MED); RESPIRATORY SYSTEM; CLINICAL MEDICINE; Clinical Medicine (MED); Solunum Bakımı; Akciğer ve Solunum Tıbbı; Respiratory Care; Pulmonary and Respiratory Medicine; Idiopathic pulmonary fibrosis; Pectoralis muscle strength; Pulmonary function test; Chest wall muscle; QUADRICEPS WEAKNESS; EXERCISE CAPACITY; LUNG-DISEASE; UPPER-LIMB; ENDURANCE; PATTERN; Idiopathic pulmonary fibrosis; Pectoralis muscle strength; Pulmonary function test; Chest wall muscle